ANALYSIS OF 2.4GHz AND 5GHz FREQUENCY CHANNELS IN HOTSPOT AREA DISTRIBUTION - Belutowe, Yohanes Suban (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Comfort of internet access when using wireless network services through hotspots is very important, as wireless networks are often said to be unstable and uncomfortable. One of the causes is the overlapping of frequency channels, which directly reduces network quality. Weak signals can lead to mobile devices not receiving a proper Internet Protocol (IP) address from the available hotspot. Mobile devices may switch to other hotspots due to an inability to maintain a signal from the intended hotspot. To prevent these issues, it is necessary to conduct a proper analysis in allocating frequency channels, specifically for the 2.4 GHz and 5 Ghz. Wireless analysis includes Wi-Fi Channel, Channel Rating, Time Graph (Signal Strength), and Signal Meter using the Android application Wi-Fi Analyzer, as well as Quality of Services (QoS) analysis using the WireShark program, which encompasses Throughput, Packet Loss, Delay, and Jitter. This way, network access speed can be maintained through proper channel management